2022
DOI: 10.1002/smll.202201300
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Hydrogel Delivering Niobium Carbide Boosts ROS‐Scavenging and Antimicrobial Activities for Diabetic Wound Healing

Abstract: cause of nontraumatic limb amputations, threatening patient health and quality of life. [1,2] Wound healing is a fascinatingly complex biological process. Traditionally, it is divided into four overlapping phases: hemostasis, inflammation, proliferation and remodeling. [3,4] Compared with the healing of other wounds, the healing of diabetic wounds gets stalled in the inflam matory phase, which is characterized by excessive production of reactive oxygen species (ROS), proinflammatory cytokines and proteases. [5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(71 citation statements)
references
References 62 publications
(88 reference statements)
0
71
0
Order By: Relevance
“…al developed an injectable thermosensitive niobium carbide (Nb 2 CT x )‐based hydrogel (Nb 2 C@Gel) with antioxidative and antibacterial properties for diabetic wound healing. [ 211 ] The hydrogel was prepared by mixing a cold aqueous solution of poly(lactic acid‐co‐glycolic acid)‐b‐poly(ethylene glycol)‐b‐poly(lactic acid‐co‐glycolic acid) (PLGA‐PEG‐PLGA) triblock copolymer with a cold aqueous dispersion of Nb 2 CT x nanosheets (an average size of 153 nm, a zeta potential of −47 mV) followed by increasing the mixture temperature to 37 °C. The hydrogel exhibited good biocompatibility with keratinocytes, fibroblasts, and endothelial cells, three main cells in wound healing.…”
Section: Applications Of Mxene As An Antibacterial Agentmentioning
confidence: 99%
“…al developed an injectable thermosensitive niobium carbide (Nb 2 CT x )‐based hydrogel (Nb 2 C@Gel) with antioxidative and antibacterial properties for diabetic wound healing. [ 211 ] The hydrogel was prepared by mixing a cold aqueous solution of poly(lactic acid‐co‐glycolic acid)‐b‐poly(ethylene glycol)‐b‐poly(lactic acid‐co‐glycolic acid) (PLGA‐PEG‐PLGA) triblock copolymer with a cold aqueous dispersion of Nb 2 CT x nanosheets (an average size of 153 nm, a zeta potential of −47 mV) followed by increasing the mixture temperature to 37 °C. The hydrogel exhibited good biocompatibility with keratinocytes, fibroblasts, and endothelial cells, three main cells in wound healing.…”
Section: Applications Of Mxene As An Antibacterial Agentmentioning
confidence: 99%
“…Prolonged nonhealing of the wound after prosthetic implantation can increase bacterial colonization and lead to wound infection. , Redox imbalance and immune disorders caused by infection exacerbate impaired wound healing and further lead to deep infection around implants. Therefore, expediting the healing of infected wounds is an effective means of preventing and treating IRIs. The Lut@Cu-HN regulates immune homeostasis by remodeling the redox balance, thereby removing bacterial infections in vitro and in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…We previously investigated the use of synthetic ADSC-exo@MMP-PEG hydrogel in wound treatment, demonstrating that it could alleviate H 2 O 2 -induced oxidative stress and rescue the impaired wound healing in diabetic mice [ 17 ]. Furthermore, the thermosensitive niobium carbide (Nb 2 C)-based hydrogel (Nb 2 C@Gel), which has antioxidant and antimicrobial activity, could promote wound healing by attenuating ROS levels [ 18 ]. A specific role of Nrf2 was highlighted in research by Simu et al, which indicated that oxidative stress could be decreased by activating Nrf2, as Nrf2 mediates ROS elimination and nitric oxide generation [ 19 ].…”
Section: Discussionmentioning
confidence: 99%